Peretinoin, an acyclic retinoid, inhibits hepatocarcinogenesis by suppressing sphingosine kinase 1 expression in vitro and in vivo. Issue 1 (December 2017) - Funaki, Masaya; Kitabayashi, Juria; Shimakami, Tetsuro; Nagata, Naoto; Sakai, Yuriko; Takegoshi, Kai; Okada, Hikari; Murai, Kazuhisa; Shirasaki, Takayoshi; Oyama, Takeru; Yamashita, Taro; Ota, Tsuguhito; et al.
Abstract Sphingosine-1-phospate is a potent bioactive lipid metabolite that regulates cancer progression. Because sphingosine kinase 1 and sphingosine kinase 2 (SPHK 1/2) are both essential for sphingosine-1-phospate production, they could be a therapeutic target in various cancers. Peretinoin, an acyclic retinoid, inhibits post-therapeutic recurrence of hepatocellular carcinoma via unclear mechanisms. In this study, we assessed effects of peretinoin on SPHK expression and liver cancer developmentin vitro andin vivo . We examined effects of peretinoin on expression, enzymatic and promoter activity of SPHK1 in a human hepatoma cell line, Huh-7. We also investigated effects of SPHK1 on hepatocarcinogenesis induced by diethylnitrosamine using SPHK1 knockout mice. Peretinoin treatment of Huh-7 cells reduced mRNA levels, protein expression and enzymatic activity of SPHK1. Peretinoin reduced SPHK1 promoter activity; this effect of peretinoin was blocked by overexpression of Sp1, a transcription factor. Deletion of all Sp1 binding sites within the SPHK1 promoter region abolished SPHK1 promoter activity, suggesting that peretinoin reduced mRNA levels of SPHK1 via Sp1. Additionally, diethylnitrosamine-induced hepatoma was fewer and less frequent in SPHK1 knockout compared to wild-type mice. Our data showed crucial roles of SPHK1 in hepatocarcinogenesis and suggests that peretinoin prevents hepatocarcinogenesis by suppressing mRNA levels of SPHK1.